007: Democratically Finding the Cause of Packet Drops - Arzani, Behnaz; Ciraci, Selim; Chamon, Luiz; Zhu, Yibo; Liu, Hongqiang; Padhye, Jitu; Loo, Boon Thau; Outhred, Geoff (NSDI '18, 2018)
Network failures continue to plague datacenter operators as their symptoms may not have direct correlation with where or why they occur. We introduce 007, a lightweight, always-on diagnosis application that can find problematic links and also pinpoint problems for each TCP connection. 007 is completely contained within the end host. During its two month deployment in a tier-1 datacenter, it detected every problem found by previously deployed monitoring tools while also finding the sources of other problems previously undetected.